Third Party Legal Protection Against Investors Does Not Release the Building Rights After Termination of Contracts for Business Sites - Rexon Manihuruk (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2018)
Legal Protection for Third Parties (Occupants: Tenants) Facing Investors who do not relinquish Building Rights After the Termination of Contract Agreement for Morning Market Business Sites in Tegal City is needed. This paper uses a normative juridical research method. The main data sources of this study come from the results of decisions and documents relating to the problems faced by traders, especially those who received complaints and were sued by Investors, including decisions between the city government and investors. Based on the results of the study it can be concluded that the role of the city of Tegal to protect traders is very important as a form of legal protection for the actions of investors against the occupants of the morning market stalls block B and C morning market in Tegal City. The Tegal City Government as having legal rights and relations (compensation/ peace agreement) after terminating the contract for the place of business with the Investor to collect the obligation of the Investor to give up his rights in a preventive and repressive manner (making a claim) to the investor to carry out its obligations as agreed surrender (release) the right to use the building.Keywords: Legal Protection; Business Place Contracts; Building Use Rights